The wind-up bird chronicle - Murakami, Haruki, 1949-; Rubin, Jay, 1941- (New York : Vintage International, 1998)
Having quit his job, Toru Okada is enjoying a pleasant stint as a "house husband", listening to music and arranging the dry cleaning and doing the cooking - until his cat goes missing, his wife becomes distant and begins acting strangely, and he starts meeting enigmatic people with fantastic life stories. They involve him in a world of psychics, shared dreams, out-of-body experiences, and shaman-like powers, and tell him stories from Japan's war in Manchuria, about espionage on the border with Mongolia, the battle of Nomonhan, the killing of the animals in Hsin-ching's zoo, and the fate of Japanese prisoners-of-war in the Soviet camps in Siberia.
"This translation originally published in hardcover in the United States by Alfred A. Knopf, Inc., New York, in 1997"--T.p. verso.
"Works consulted," p. [609].
Includes a list of author's works ([p. 612-613]).
Keywords: Japan -- Fiction; Japan -- Politics and government -- Fiction; Man-woman relationships -- Japan -- Fiction; Psychological fiction